1988
DOI: 10.1073/pnas.85.20.7743
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody identification of a 100-kDa membrane protein in HeLa cells and human spinal cord involved in poliovirus attachment.

Abstract: Unique receptor sites for poliovirus are considered to be the primary determinant of the virus' cell and tissue-type specificity. To study the poliovirus-cell interaction, eight monoclonal antibodies that specifically block the cytopathic effects of poliovirus were generated by using HeLa cell preparations as immunogen and a newly developed colorimetric screening assay. Plaque-inhibition assays confirmed the viral specificity of the antibodies, and when one antibody,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

1989
1989
2000
2000

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 25 publications
(21 reference statements)
1
38
1
Order By: Relevance
“…Some of our results showed that poliovirus replication in human endothelial cells might be involved in poliovirus transport across the blood-brain barrier (Couderc et aL, 1989b). The study of poliomyelitis pathogenesis will be benefited by using knowledge acquired from new data emerging from molecular characterization of the cellular poliovirus receptor (Shepley et al, 1988;Mendelsohn et al, 1989). Molecular probes which detect poliovirus receptor transcripts will help define human tissues susceptible to virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Some of our results showed that poliovirus replication in human endothelial cells might be involved in poliovirus transport across the blood-brain barrier (Couderc et aL, 1989b). The study of poliomyelitis pathogenesis will be benefited by using knowledge acquired from new data emerging from molecular characterization of the cellular poliovirus receptor (Shepley et al, 1988;Mendelsohn et al, 1989). Molecular probes which detect poliovirus receptor transcripts will help define human tissues susceptible to virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…This was repeated until passage 6. Plaque purification of virus was done at 39.5°C similarly to plaque assays except that cells were stained as described by Shepley et al (52). Plaques of different sizes were picked through the agar with disposable tips attached to a micropipettor.…”
Section: Methodsmentioning
confidence: 99%
“…The cellular receptors have now been isolated for both poliovirus (Mendelsohn et al, 1986(Mendelsohn et al, , 1989Shepley et al, 1988) and the major group rhinoviruses (Greve et al, 1989;Staunton et al, 1989); however, the attachment of HAV has not been characterized extensively (Seganti et al, 1987(Seganti et al, , 1989. Viruses can interact with cells in a variety of ways (Dimmock, 1982;Hsu et al, 1988;Marsh & Helenius, 1989;Reagan et al, 1984); in addition to attaching to specific receptors, it has been shown that viruses can bind by indirect mechanisms, for example the attachment of dengue virus to cells bearing Fc receptors is enhanced by antibody raised to the virus (Halstead & O'Rourke, 1977), whereas cytomegalovirus exploits flz-microglobulin in its interaction with cells (Grundy et al, 1987).…”
Section: Introductionmentioning
confidence: 99%